2010
DOI: 10.5037/jomr.2010.1203
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonate-Related Osteonecrosis of the Jaw Bone: Radiological Pattern and the Potential Role of CBCT in Early Diagnosis

Abstract: ObjectivesTo systematize the clinico-radiological symptoms and course of bisphosphonate-related osteonecrosis of jaw bone and toevaluate the diagnostic potential of various radiological techniques to detect mild osteonecrosis in each stage of the disease.Material and MethodsThe sample consisted of 22 patients previously diagnosed with extraoral malignant disease. Diagnosis was based on a clinical examination in conjunction to digital panoramic radiography and cone beam computed tomography (CBCT). Two dentomaxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 20 publications
2
43
1
8
Order By: Relevance
“…Sur le plan radiologique, le cone beam serait plus performant dans le diagnostic précoce de l'ostéonécrose que le denta-scanner [15]. Il existe plusieurs classifications de l'ostéonécrose induite par les biphosphonates, celle de Ruggiero et al, en 2009, propose quatre stades d'évolution avec des aspects clinico-radiologiques variables : − stade 0 : aucun signe clinique apparent de nécrose osseuse mais présence de signes et symptômes cliniques non spé-cifiques ; − stade 1 : nécrose osseuse apparente chez des patients asymptomatiques sans infection associée ; − stade 2 : nécrose osseuse apparente associée à une infection avec présence de douleurs et d'érythème dans la zone exposée avec ou sans écoulement purulent ; − stade 3 : nécrose osseuse apparente associée à un ou plusieurs des signes suivants : nécrose osseuse apparente s'étendant au-delà de l'os alvéolaire (bord basilaire et bord postérieur du ramus mandibulaire, sinus maxillaire et zygoma) entraînant fracture, fistule extra-orale, communication bucco-sinusienne, ou ostéolyse s'étendant au bord inférieur mandibulaire ou au plancher sinusien [25]. Notre patiente présentait une ostéonécrose de stade 3 selon cette classification.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Sur le plan radiologique, le cone beam serait plus performant dans le diagnostic précoce de l'ostéonécrose que le denta-scanner [15]. Il existe plusieurs classifications de l'ostéonécrose induite par les biphosphonates, celle de Ruggiero et al, en 2009, propose quatre stades d'évolution avec des aspects clinico-radiologiques variables : − stade 0 : aucun signe clinique apparent de nécrose osseuse mais présence de signes et symptômes cliniques non spé-cifiques ; − stade 1 : nécrose osseuse apparente chez des patients asymptomatiques sans infection associée ; − stade 2 : nécrose osseuse apparente associée à une infection avec présence de douleurs et d'érythème dans la zone exposée avec ou sans écoulement purulent ; − stade 3 : nécrose osseuse apparente associée à un ou plusieurs des signes suivants : nécrose osseuse apparente s'étendant au-delà de l'os alvéolaire (bord basilaire et bord postérieur du ramus mandibulaire, sinus maxillaire et zygoma) entraînant fracture, fistule extra-orale, communication bucco-sinusienne, ou ostéolyse s'étendant au bord inférieur mandibulaire ou au plancher sinusien [25]. Notre patiente présentait une ostéonécrose de stade 3 selon cette classification.…”
Section: Discussionunclassified
“…Notre patiente présentait une ostéonécrose de stade 3 selon cette classification. Selon la SDCEP (Scottish Dental Clinical Effectiveness Programme), les patients diagnostiqués avec OI sont placés dans la catégorie « risque élevé » de développer une ostéonécrose [11], ce risque est lié au traitement mais aussi à la nature de la maladie caractérisée par une fragilité du tissu conjonctif [25]. Cependant une revue systémique de la prévalence de l'ostéonécrose chez les patients atteints de l'OI traités par biphosphonates a montré qu'aucun cas d'ostéonécrose n'a été détecté chez ces patients [11,23].…”
Section: Discussionunclassified
“…22 It was shown that, especially in the mandible, with progression of the severity of the BRONJ lesion, formation of new periostal bone increases. 20,22,23 In a periodontal disease induced BRONJ rat model, Aghaloo et al 24 reported increased periosteal new bone formation and wider alveolar bone on microCT images. Intermittent parathyroid hormone administration was also shown to induce an increase in alveolar bone formation in rats.…”
Section: Discussionmentioning
confidence: 99%
“…17 Recent studies reported that CT is one of the most useful imaging modalities in BRONJ cases; however, the radiological signs are not specific for BRONJ. [18][19][20][21] Although radiological interpretation is crucial for the definition of BRONJ lesions, in cases that necrotic bone is present but not yet exposed into the oral cavity, radiographic images may also appear normal. 22 Unfortunately, there is only a limited number of publications about the diagnostic importance of radiological evaluation in these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…53 Another advantage of CBCT over CT is its better spatial resolution, providing images with submillimetre isotropic voxel resolution ranging from 0.4 mm to as low as 0.076 mm. 46 Images obtained during the reconstruction process in CBCT have a level of spatial resolution accurate enough for metric analysis, 44,46,54 with precision in all dimensions 46 and showing a very clear anatomy of the maxillofacial bones. 52 Nevertheless, CBCT attenuation analysis is not as reliable as that in CT, showing a lower soft-tissue contrast.…”
Section: Imaging Findingsmentioning
confidence: 99%